The Influence of Service Quality, Brand Image and Price Regarding J&T Express Drop Center Customer Satisfaction Ciomas, Bogor Regency - Agus Setiawan; Rachmat Gunawan; Palahudini (MultiTech Publisher, 2024)
This research aims to determine consumer responses regarding service quality, brand image, price, and consumer satisfaction and determine the influence of service quality, brand image, and price on consumer satisfaction at the J&T Express Drop Center Ciomas. The method used in this research is quantitative descriptive and verification. The sample used in the study was 98 in distributing the questionnaire. The data analysis technique uses an ordinal scale that analyzes multiple regression, multiple correlation analysis, coefficient of determination analysis, and hypothesis testing. Consumer responses to service quality and brand image are sufficient, consumer responses to price are dissatisfied and responses to consumer satisfaction are adequate. The research results show that service quality, brand image, price, and consumer satisfaction simultaneously and partially have a positive and significant effect on consumer satisfaction at the J&T Express Drop Center Ciomas, Bogor Regency.